Predictive Factors for Surgical Intervention in Neonates with Necrotizing Enterocolitis: A Retrospective Study - Yu, Lei; Liu, Chao; Du, Qingjing; Ma, Lishuang (Frontiers in Surgery, 2022)
Background The current indications based on the clinicopathological parameters for predicting the need for surgery in neonatal necrotizing enterocolitis (NEC) are still limited. This study retrospectively analyzes the characteristics of neonatal NEC and aims to identify the risk factors for surgical intervention in NEC. Methods Data of the NEC cases from 2015 to 2019 were collected from our institution and divided into two groups: surgical group (n = 41) and conservative treatment group (n = 143). Clinical, physical, and laboratory measures were analyzed by univariate analysis and multivariate logistic regression. The diagnostic values and receiver operative characteristic (ROC) curve were used for the assessment. Results Univariate analysis identified significant differences between the surgical group and the conservative group in a series of clinical, physical, and laboratory measures (all p < 0.05). The results of multivariate logistic regression analysis showed that procalcitonin (adjusted OR: 167.1, 95% CI, 3.585–7,788.758, p = 0.009) and gestational age (adjusted OR: 0.85, 95% CI, 0.77–0.94, p = 0.001) were independent surgical indications for NEC. The results from ROC curve and diagnosis values demonstrated that procalcitonin [the area under the curve (AUC) = 0.864], CRP (AUC = 0.783) and fibrinogen (AUC = 0.720) had good predictive performance for surgical NEC. Conclusions The level of procalcitonin and gestational age were found to be independent surgical indications for neonates with NEC.